Modelling of compressive behaviour of concrete-like materials at high strain rate - Zhou, X.; Hao, Hong (Elsevier, 2008)
Uniaxial compression tests are the most common tests for characterizing the strength of concrete-like materials. The dynamic compression strength of concrete-like material is typically obtained by Split Hopkinson Pressure Bar (SHPB) tests. The increase in material strength under dynamic loading is usually attributed to the strain rate effect and modelled with a dynamic increase factor (DIF). However, it was observed by some researchers that the radial inertial confinement caused apparent increase of dynamic strength of concrete-like specimen in SHPB tests. They attributed the material strength increase to this inertial effect, instead of the strain rate effect. In the present study, numerical analyses are performed to investigate the compressive behaviour of concrete-like material at high strain rates. A homogeneous macroscale model and a heterogeneous mesoscale model are developed in the study. In the macroscale model, the material is assumed to be homogeneous and isotropic. In the mesoscale model, the test sample is modelled as a three-phase composite consisting of aggregate, mortar matrix and interfacial transaction zone (ITZ) between the aggregate and the mortar matrix. The aggregate is assumed to be circular and the ITZ is modelled as a thin boundary around the aggregate. In the both models, the materials are assumed to be insensitive to the strain rate first. Therefore, the obtained strength enhancement is only due to the inertial confinement. Strain rate sensitive material properties are then used in the two models in the calculations. Numerical simulations of the concrete samples under compression at different strain rates are carried out. The relative contribution of the inertial effect and the strain rate effect on the compressive strength DIF is examined based on the numerical results. The failure process of concrete specimen is also studied.